Fauna and Flora Describes in Holy Land with Sixteen Age Polish Pilgrims Relations - Ossowska, Katarzyna (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The area of the Holy Land is called “The Land flowing milk and honey”. The first Polish pilgrims who came to the Holy Land already paid attention to the diversity of its fauna and flora and this is confirmed by the descriptions of their journeys. Thanks to the 16th century description of the Holy Land by Anzelm Polak, Jan Tarnowski, Jan Goryński and Mikołaj Krzysztof Radziwiłł Sierotka it is possible to check whether something especially and invariably intrigued Poles in the Middle Eastern nature. The purpose of the article is to create a list of key fragments with the themes of fauna and flora from the itineraries of the travelers mentioned. The collected material will allow us to look at nature, as it was seen by the 16th century Polish pilgrims. The presentation opens with a description of the Polak’s peregrination, and will finish with the description of Radziwiłł Sierotka. The chronological order and the scheme: presentation of the author, description of the source and its discussion will apply to each artifact. In all relations to a greater or lesser extent, were found exotic expression of the Middle Eastern nature. Pilgrims took notes of the most characteristic animals and plants found in the Holy Land. The list of texts is also emphasized by their individual values and deficiencies, which were not previously noticed by scientists.